2015
DOI: 10.2306/scienceasia1513-1874.2015.41.251
|View full text |Cite
|
Sign up to set email alerts
|

Variability in chemical and mechanical properties of Pará rubber (Hevea brasiliensis) trees

Abstract: Pará rubber (Hevea brasiliensis) is grown primarily for latex. Some clones (timber clones) are frequently planted for wood production. Rubberwood, from old rubber trees, is an important economic byproduct. In general, the quality of the wood depends on multiple factors, including chemical and mechanical properties. This study investigates the effects of clone variety, height (1.3 and 6.0 m above ground level), and the variation between clone and height on chemical and mechanical properties of seven Pará rubber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
4
0
4
Order By: Relevance
“…Depending on the type of adhesive and the density of the wood, the adhesive can penetrate three to five cells, filling the open cells or covering its internal walls (Sellers Junior, 1994). The literature reports results for apparent density for rubberwood of 0.572 g cm -3 (Iwakiri et al, 2017) and 0.590 g cm -3 (Riyaphan et al, 2015), therefore, the values observed in this work are close to those observed in the literature.…”
Section: Physical Properties Of Rubberwood Treated With Cca Ccb and supporting
confidence: 90%
“…Depending on the type of adhesive and the density of the wood, the adhesive can penetrate three to five cells, filling the open cells or covering its internal walls (Sellers Junior, 1994). The literature reports results for apparent density for rubberwood of 0.572 g cm -3 (Iwakiri et al, 2017) and 0.590 g cm -3 (Riyaphan et al, 2015), therefore, the values observed in this work are close to those observed in the literature.…”
Section: Physical Properties Of Rubberwood Treated With Cca Ccb and supporting
confidence: 90%
“…Os resultados verificados para a análise estatística (ANOVA), para os resultados de densidade básica indicaram não haver diferença significativa. Valores similares foram observados por Riyaphan et al (2015), apresentando densidade básica média de 0,551 g/cm³.…”
Section: Resultsunclassified
“…Os teores médios de extrativos totais obtidos mostraram-se inferiores aos encontrados por Riyaphan et al (2015), para árvores de Hevea brasiliensis, provenientes da Malásia, cujos valores médios foram de 9%. O teor de extrativos da madeira é de fundamental importância visando a fabricação de celulose, pois resulta em maior demanda de reagentes químicos na polpa celulósica, com consequente redução do rendimento, inibições de reações, incrustações de materiais na polpa e nos equipamentos, corrosão e dificuldades no branqueamento (GOMES, 2007).…”
Section: Resultsunclassified
“…A determinação da densidade é um fator indispensável para a fabricação de elementos de madeira laminada colada, visto que a mesma pode interferir na penetração da cola, pressão utilizada, tempo necessário para prensagem e cura do adesivo (Segundinho et al, 2018). De acordo com a classificação de Coradin et al (2010) e Silveira et al (2013), as madeiras utilizadas nesta pesquisa são consideradas de média densidade, pois apresentam valores médios para densidade básica entre 0,50 g.cm-³ e 0,72 g.cm -³. Para a madeira de seringueira foi obtido teor médio de extrativos de 5,25%, inferior ao valor obtido por Riyaphan et al (2015), que analisaram a mesma espécie, oriunda da Malásia com 13 anos de idade, em duas posições do fuste e obtiveram valor médio de 9,75% de extrativos totais. Faria et al (2019a) fizeram um estudo com a mesma espécie, proveniente da região Sul do estado de MG (Brasil), com 20 anos de idade e obtiveram valor inferior ao obtido na presente pesquisa para o teor de extrativos (3,17%).…”
Section: Densidade Básica E Análise Química Dos Materiais Lignocelulósicosunclassified